2018
DOI: 10.4070/kcj.2017.0328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non-vitamin K Antagonist Oral Anticoagulants in Atrial Fibrillation Patients with Newly Diagnosed Cancer

Abstract: Background and ObjectivesThere are limited data on the use of non-vitamin K antagonist oral anticoagulants (NOACs) in atrial fibrillation (AF) patients with cancer. We aimed to assess the efficacy and safety of NOACs in AF patients with cancer in this study.MethodsIn 2,568 consecutive non-valvular AF patients with newly diagnosed cancer, we analyzed ischemic stroke/systemic embolism (SE), major bleeding, and all-cause death. Based on propensity score matching, 388 matched pairs were included in the NOAC and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 33 publications
1
65
0
Order By: Relevance
“…The two classes have differential features (convenience, half-life, use in kidney failure, availability of reversal agents, drug interaction profile) that should be used to find the optimal agent for each patient. A possible exception are Asian patients, a population where DOACs appear consistently better than VKA in patients with cancer, consistent with the greater net benefit seen in Asians over non-Asians in the general population [48,87,88].…”
Section: What Is the Ideal Anticoagulant Agent For Patients With Cancmentioning
confidence: 71%
See 2 more Smart Citations
“…The two classes have differential features (convenience, half-life, use in kidney failure, availability of reversal agents, drug interaction profile) that should be used to find the optimal agent for each patient. A possible exception are Asian patients, a population where DOACs appear consistently better than VKA in patients with cancer, consistent with the greater net benefit seen in Asians over non-Asians in the general population [48,87,88].…”
Section: What Is the Ideal Anticoagulant Agent For Patients With Cancmentioning
confidence: 71%
“…Some of the most common cancers, i.e., breast and prostate cancer, have either only a very small or no increase in stroke [3,42,46]. Concerning the latter, patients with metastatic cancer or with a recent diagnosis of cancer have a higher risk of stroke than those that are disease-free [3,4,42,[47][48][49][50]. Therefore, the claim that cancer (i.e., all and any cancer) should be added to CHA 2 DS 2 VASc is a simplistic one and should be nuanced before any serious proposals are put forward.…”
Section: Should Cancer or Cancer Type Be Considered A Risk Factor Formentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent article in Korean Circulation Journal , Kim et al 6) investigated the efficacy and safety of NOACs among patients with AF and newly diagnosed cancer. In their retrospective and propensity score matched study, Kim et al 6) reported the incidence of stroke/systemic embolism (SE), all-cause mortality, and major bleeding event were significantly lower in NOACs treated group as compared to those with warfarin. In addition, these results were not affected by different type or reduced dosage of NOACs.…”
mentioning
confidence: 99%
“…However, only one-fifth patients of the warfarin treated group achieved TTR of ≥60% and this result reflects difficulty of maintaining stable INR range in the warfarin treated group, maybe because of metabolic interactions with chemotherapy agents and antibiotics, chemotherapy-induced pancytopenia, dehydration due to poor oral intake, and the frequent need for surgical or invasive procedures. Unfortunately, Kim et al 6) did not report data regarding medications including chemotherapy agents and type of active cancer, and all of which makes the net benefit of NOACs therapy versus warfarin uncertain. Moreover, this limitation raises another questions as to whether reduced dosed NOACs suffice in the setting of active cancer and AF because many chemotherapy agents have significant interaction with the CYP3A4 enzyme which can alter the drug level of NOACs and chemotherapy may lead to higher bleeding risk as well.…”
mentioning
confidence: 99%